DEVELOPMENT AND IMPLEMENTATION OF OPTIMIZATION AND AUTOMATION METHODS FOR CREATING AND ANIMATING 3D CHARACTERS USING FRAMEWORKS FOR CONTROLLING BONE STRUCTURES IN BLENDER (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Efficient, flexible, automated means of character creation and animation are in demand due to the quick transformations in digital content creation and real-time rendering technologies. The old workflows of character rigging and bone manipulation for animation never were really in favor of creative scaling and iterative capability as they were quite demanding time-wise with rather manual intervention required. In this paper, a new framework is suggested for optimizing and automating the processes of 3D character creation and animation, with special attention paid to procedural bone generation and control in Blender.